2019
DOI: 10.1177/1758835919841946
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in the medical management of gastrointestinal stromal tumours

Abstract: The tyrosine kinase inhibitor (TKI) imatinib has radically changed the natural history of KIT-driven gastrointestinal stromal tumours (GISTs). Approved second-line and thirdline medical therapies are represented by the TKIs sunitinib and regorafenib, respectively. While imatinib remains the cardinal drug for patients with GISTs, novel therapies are being developed and clinically tested to overcome the mechanisms of resistance after treatments with the approved TKI, or to treat subsets of GISTs driven by rarer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 88 publications
(122 reference statements)
0
30
0
Order By: Relevance
“…For third-line treatment, top-line results of the phase III VOYAGER trial comparing avapritinib to regorafenib has shown no statistical difference in PFS, although ORR was higher in the avapritinib cohort. A recent review has suggested a complete shift in second-line and third-line treatment with sunitinib and regorafenib being replaced by ripretinib and avapritinib [28]. In the same publication, an alternative flow chart is presented in which both drugs are followed by 'other tyrosine kinase inhibitors' in fourth line and beyond [28].…”
Section: Imatinib Reintroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For third-line treatment, top-line results of the phase III VOYAGER trial comparing avapritinib to regorafenib has shown no statistical difference in PFS, although ORR was higher in the avapritinib cohort. A recent review has suggested a complete shift in second-line and third-line treatment with sunitinib and regorafenib being replaced by ripretinib and avapritinib [28]. In the same publication, an alternative flow chart is presented in which both drugs are followed by 'other tyrosine kinase inhibitors' in fourth line and beyond [28].…”
Section: Imatinib Reintroductionmentioning
confidence: 99%
“…A recent review has suggested a complete shift in second-line and third-line treatment with sunitinib and regorafenib being replaced by ripretinib and avapritinib [28]. In the same publication, an alternative flow chart is presented in which both drugs are followed by 'other tyrosine kinase inhibitors' in fourth line and beyond [28]. However, the overwhelming responses of PDGFRA D842V-mutated GISTs to avapritinib were not included.…”
Section: Imatinib Reintroductionmentioning
confidence: 99%
“… 1 , 2 Clinical benefits from the administration of REG were initially observed in metastatic colorectal cancer (CRC) and gastrointestinal stromal tumour (GIST), as stated by the three randomized controlled clinical trials (RCTs) CORRECT, GRID and CONCUR. 3 5 More recently, REG gained approval in hepatocellular carcinoma (HCC), on the basis of data from the RESORCE trial, 6 where REG showed a survival benefit in patients affected by advanced or metastatic HCC who progressed on sorafenib treatment. Currently, REG is approved as a single agent for the treatment of CRC, GIST and HCC at a dose of 160 mg orally once daily on days 1–21 of each 28 days cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Prompt identification of AEs is fundamental to guarantee that patients can be treated as safely as possible and, in order to ensure that anticancer treatment is effective, maintaining the optimal dose levels represents a major issue. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…2 GIST responds to treatment with targeted KIT/PDGFRA inhibitors such as imatinib mesylate. [3][4][5] However, up to 40-50% of GISTs develop secondary resistance after an average of 24 months of imatinib treatment. Based on the natural evolution of the disease, the patient could be placed on a higher dose of imatinib or a tyrosine kinase inhibitor such as ripretinib, though resistance can be a challenge.…”
Section: Introductionmentioning
confidence: 99%